Education and Social Change - Ismail Muhammad; Safrina Ariani; Aisyah Idris (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
In human life, change is inevitable. neither preventable nor deniable. Humans must adapt in order to live safely, constructively, and avoid being overtaken by social changes and the times. In order to explain the connection between education and social change, this essay was written utilising the library research method and library references in all of its forms. The findings of thestudy show that a number of facets of education, including management, curriculum, methods, media, psychology, evaluation, and teacher preparation, will be directly impacted by social change